Analisis Statik dan Dinamik Struktur Tranduser pada Low-Cost Dynamometer untuk Mengukur Gaya Potong Proses Bubut Orthogonal - Alfiyani, Risma; Susanto, Agus; Rezika, Wida Yuliar; Wicaksono, Ramadhana Eka; Mudmainah, Putri Hana Widyaning (Universitas Katolik Parahyangan, 2024)
Cutting forces in turning process are usually measured using dynamometer and they can be used to evaluate the quality of the cutting process. Commercial dynamometers on the market today offered with quite expensive prices. Therefore, many researchers are trying to design dynamometers at more affordable prices. One of the most important components in designing a dynamometer is tranducer. This article discusses the design and static and dynamic analysis of a full octagonal shaped ring tranducer for measuring cutting forces in orthogonal cutting. The tranducer design is analysed statically using the Finite Element Method (FEM) and dynamically using the Experimental Modal Analysis (EMA) method to determine its structural strength. The results of the static analysis of the strength of the tranducer structure were able to withstand static loads of 224 to 388 N. It is because the tranducer stress did not exceed the yield strength of the material which is 233 MPa. While the dynamic analysis of the tranducer structure using EMA shows that the natural frequency, the damping ratio, the stiffness constant, the modal mass, and the damping coefficient 3851 Hz, 18.5 x 106 N/m, 1.04%, 32 g, and 16 N/s/m, respectively. With these dynamic parameter, the tranducer design for this low-cost dynamometer is safe and reliable when used in the turning process with spindle rotation speeds reaching 20 Krpm.